"Social Crimes": Understandings of HIV/AIDS as a Disease Among Grandparents Raising Grandchildren in Vietnam. Issue 6 (18th September 2016) - Harris, Lesley M.; Boggiano, Victoria; Nguyen, Duy Thang
Abstract : Grandparent caregivers are vital to the survival of grandchildren who are orphaned and who have been affected by HIV/AIDS. The purpose of this qualitative study was to understand the meaning of HIV as a disease among grandparents raising grandchildren orphaned by HIV/AIDS in northern Vietnam and to gain insight into how this understanding affected grandparents' relationships and health-seeking decisions. Results indicated that grandparents had knowledge deficits about the biomedical aspects of the disease and often hid their grandchildren's HIV status or preferred not to seek testing. Effective interventions must address stigma reduction, family relationships, and access to health care to increase testing and treatment of grandchildren.